Perfluorocarbon improves post-transplant survival and early kidney function following prolonged cold ischemia - Marada, T; Zacharovova, K; Saudek, F (European surgical research. Europaische chirurgische Forschung. Recherches chirurgicales europeennes, 2010)
BACKGROUND: The two-layer organ preservation method (TLM) based on oxygenated perfluorocarbon overlaid with University of Wisconsin (UW) solution has been successfully used in clinical islet and experimental heart and intestine transplantation. We tested whether this technique would prevent tissue damage and improve kidney function in a model of syngeneic kidney transplantation with prolonged ischemia time. METHODS: Kidneys were stored for 24 h either in UW solution (n = 16), with TLM (n = 16) or transplanted immediately (control group, n = 12). In half of the animals, survival was observed and in the other animals grafts were procured for semiquantitative histological scoring and TUNEL apoptosis assessment 24 h after transplantation. RESULTS: One-month survival rates in the UW, TLM and control groups were 12.5, 62.5 and 100%, respectively (UW vs. TLM, p < 0.01). Median creatinine levels 24 h after transplantation were 381, 299 and 121 microM, respectively (UW vs. TLM, p < 0.02). Histological scoring showed more severe tissue damage in the UW group than in the TLM group (p < 0.05). Apoptosis was more frequent in the UW group than in the TLM group (p < 0.05). CONCLUSION: We demonstrated for the first time that conservation with TLM significantly improves the outcome of kidney transplantation in a rat model and should therefore be further studied in larger animals.
Keywords: Animals; Kidney; apoptóza; Adenosine; krevní náhražky; reperfuzní poškození; glutathion; potkani inbrední BN; studená ischemie; transplantace izogenní; roztoky pro uchovávání orgánů; rafinosa; Glutathione; Apoptosis; adenosin; časové faktory; Time Factors; Rats, Inbred BN; Insulin; alopurinol; transplantace ledvin; Fluorocarbons; uchovávání orgánů; Raffinose; Kidney Transplantation; Allopurinol; Male; Blood Substitutes; Cold Ischemia; Reperfusion Injury; Creatinine; Graft Survival; Organ Preservation Solutions; krysa rodu Rattus; kreatinin; zvířata; mužské pohlaví; Organ Preservation; Transplantation, Isogeneic; ledviny; inzulin; přežívání štěpu; Rats; fluorokarbony